The effect of residual palladium catalyst contamination on the photocatalytic hydrogen evolution activity of conjugated polymers - Kosco,J; Sachs,M; Godin,R; Kirkus,M; Francas,L; Bidwell,M; Qureshi,M; Anjum,D; Durrant,JR; McCulloch,I (Advanced Energy Materials, 2018)
The effect of residual Pd on hydrogen evolution activity in conjugated polymer photocatalytic systems is systematically investigated using colloidal poly(9,9-dioctylfluorene-alt-benzothiadiazole) (F8BT) nanoparticles as a model system. Residual Pd, originating from the synthesis of F8BT via Pd catalyzed polycondensation polymerization, is observed in the form of homogeneously distributed Pd nanoparticles within the polymer. Residual Pd is essential for any hydrogen evolution to be observed from this polymer, and very low Pd concentrations (<40 ppm) are sufficient to have a significant effect on the hydrogen evolution reaction (HER) rate. The HER rate increases linearly with increasing Pd concentration from <1 ppm to approximately 100 ppm, at which point the rate begins to saturate. Transient absorption spectroscopy experiments support these conclusions, and suggest that residual Pd mediates electron transfer from the F8BT nanoparticles to protons in the aqueous medium.